Dysbiosis in inflammatory bowel diseases: egg, not chicken - Stange, Eduard F. (Frontiers in Medicine, 2024)
There is agreement that inflammatory bowel diseases are, both in terms of species composition and function, associated with an altered intestinal microbiome. This is usually described by the term “dysbiosis,” but this is a vague definition lacking quantitative precision. In this brief narrative review, the evidence concerning the primary or secondary role of this dysbiotic state is critically evaluated. Among others, the following facts argue against a primary etiological impact: 1) There is no specific dysbiotic microbiome in IBD, 2) the presence or absence of mucosal inflammation has a profound impact on the composition of the microbiome, 3) dysbiosis is not specific for IBD but linked to many unrelated diseases, 4) antibiotics, probiotics, and microbiome transfer have a very limited therapeutic effect, 5) the microbiome in concordant twins is similar to disease-discordant twins, and 6) the microbiome in relatives of IBD patients later developing IBD is altered, but these individuals already display subclinical inflammation.